Factors Influencing Curriculum Leadership of Primary and Secondary School Teachers from the Perspective of Field Dynamic Theory: An Empirical Investigation in China - Junyuan Chen (MDPI AG, 2021)
Teacher curriculum leadership is in urgent demand to promote the sustainable advancement of curriculum reform, and an important guarantee for the sustainable development of students. It is of important theoretical and practical significance to clarify the influencing factors of the use and the development of teachers’ curriculum leadership. Based on Lewin’s field dynamic theory, this study conducts a multiple linear regression analysis on the data of 19,521 primary and secondary school teachers in 20 provinces of China, and investigates the influencing factors of teacher curriculum leadership from individual and school fields. The results show that individual field factors are the driving force for teachers to exert and develop curriculum leadership. When teachers have internal leading motivation, the school environment becomes an important inducing force. This finding confirms the realistic rationality of the field dynamic theory, and provides a clear direction for formulating relevant policies and practical plans for enhancing teacher curriculum leadership. That is, it is necessary to fully stimulate the internal motivation of teachers for curriculum leadership, but also to create a school environment for teachers to exercise and develop curriculum leadership.